Perforating Ocular Sickle Knife Trauma: a Case report: Poster Presentation - Case Report - Ophthalmologist - DEWI KANIA MAEMUNAH (Majalah Oftalmologi Indonesia, 2023)
Introduction : Perforating ocular injury can lead to disability or even mortality. Most individuals sustaining eye injuries are male in young age. This is a report of an extreme case when a sickle knife stabbed in the right eye of a young male cause perforating of the eyeball. Case Illustration : Seventeen years old young male presented to Emergency Room of Sukabumi Regional Public Hospital with pain and bleeding in his right eye an hour before. He had been hacked during a brawls. There was a wound in the right supraorbita area and a big sickle knife stuck in the head and tear the eye ball. Visual acuity was no light perception in his right eye. Anterior segment examination of the right eye revealed perforated sclera and cornea. X-ray examination showed fracture of the roof of the right orbit and a metal object had stuck into the Orbits. The sickle knife extraction, enucleation and superior orbit reconstruction of the right eye was done. Discussion : Identification of wounds caused by sharp metal foreign body is very important for the subsequent treatment of injuries. If the eyeball cannot be preserved, then enucleation can't be avoided. In this case, hard impact of sharp object around of the eye are also cause fracture of superior orbital rim. Reconstruction of the orbital roof using titanium and micro screws given the most stable and effective results. Conclusion : Removing a metal foreign body and anatomical defect management is important for a good outcome.